Hubungan Komunikasi Terapeutik dengan Kecemasan Pasien Pre Opeasai Apendisitis : Systematic Literature Review - Yulia Luginasari; Akhmad Faozi; Delli Yuliana Rahmat (Malahayati Nursing Journal, 2024)
ABSTRACT Appendicitis is a common inflammatory bowel disease that sometimes requires surgical intervention. The surgery for appendicitis is called an appendectomy. The surgical procedure for appendicitis can cause anxiety in patients, and one way to manage this anxiety is through therapeutic communication. Therapeutic communication is conducted by nurses with patients with the aim of promoting the patient's recovery. The objective of this study is to determine the relationship between therapeutic communication by nurses and preoperative anxiety in appendicitis patients. The method used in this study is a literature review using databases such as Google Scholar and ScienceDirect, including articles in both English and Indonesian. A total of 5 relevant articles were selected for review. The results of this study indicate that there is a relationship between therapeutic communication and preoperative anxiety in appendicitis patients. Therapeutic communication conducted by nurses has a positive impact on preoperative patients because it fosters trust and increases knowledge, thereby reducing patient anxiety. Keywords: Therapeutic Communication, Anxiety Level, Pre Operative, Apendisitis ABSTRAK Apendisitis adalah radang usus yang umum dan sering memerlukan operasi. Apendektomi adalah operasi yang dilakukan untuk mengobati apendisitis. Pasien dapat mengalami kecemasan karena prosedur operasi ini. Salah satu cara untuk mengurangi kecemasan adalah dengan berbicara dengan orang lain secara terapeutik. Interaksi yang dilakukan untuk membantu pasien sembuh disebut komunikasi terapeutik. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada hubungan antara komunikasi terapeutik yang dilakukan oleh perawat dan tingkat kecemasan pasien sebelum operasi apendisitis. Metode penelitian ini menggunakan database dalam bahasa Inggris dan Indonesia seperti Google Scholar dan Sciencedirect untuk melakukan tinjauan literatur, yang menghasilkan lima artikel yang relevan. Hasil penelitian menunjukkan bahwa komunikasi terapeutik dan kecemasan pasien sebelum operasi apendisitis berkorelasi. Pasien praoperasi mendapat manfaat dari komunikasi terapeutik perawat karena meningkatkan kepercayaan mereka dan meningkatkan pengetahuan mereka, sehingga mengurangikecemasan pasien. Kata Kunci: Komunikasi Terapeutik, Kecemasan, Pre Operasi, Apendisitis